Dynamic Charging of Electric Vehicle with Negligible Power Transfer Fluctuation - Alam, M.M.; Mekhilef, Saad; Seyedmahmoudian, M.; Horan, B. (MDPI, 2017)
High-efficiency inductive power transfer (IPT) with low misalignment effects is a key issue in the dynamic charging of electric vehicle (EV) systems. In this study, an advanced concept of analysis and design of transmitter and receiver coils with a special coil assembly is proposed for the dynamic charging of EVs. In each transmitter coil, large rectangular section is series connected with two zigzag-shaped small rectangular sections. These small sections are back-to-back series connected and located inside the large rectangular section. An adjacent pair of proposed transmitter coils with back-to-back series connection named extended double D (DD)-shaped transmitter is used throughout this paper. The major contribution in the case of the extended DD transmitter is negligible power transfer fluctuation, regardless of any horizontal misalignment of the receiver coil. Justification of the coil design is performed based on its load independent voltage gain and power transfer fluctuation characteristics. Experimental results prove that the power transfer fluctuation with load independent voltage gain is within ±6%, and the efficiency is approximately 93% under horizontal misalignment of receiver coil with an air gap of 140 mm. Finally, a new coil design set with a special arrangement has been proposed to maintain nearly uniform coupling factor and negligible power transfer fluctuation.